[Clinical and economic evaluation of the introduction of the combinazion trametinib + dabrafenib in the management of advanced melanoma in the Italian market] - Pradelli, Lorenzo; Ascierto, Paolo (Farmeconomia. Health economics and therapeutic pathways, 2016)
Melanoma is the most aggressive type of all skin cancers. In Italy the incidence is increasing both in men and in women with 13,800 new cases expected in 2016. The advanced melanoma therapy has changed in recent years with the use of immunotherapy and targeted therapies. In particular, treatment with BRAF inhibitors in patients with advanced BRAF V600 mutated melanoma has shown high rates of rapid response and survival. Due to development of acquired resistance with disease progression the rapid response observed with BRAF inhibitor therapy is not long lasting. Combining a BRAF inhibitor with a MEK inhibitor may help to delay the development of resistance and to enhance the antitumor activities with a further increase in the response and survival rate. Trametinib, an inhibitor of MEK kinases, and dabrafenib, an inhibitor of BRAF kinase, have authorizations as monotherapies and in combination with each other for treating adults with unresectable or metastatic melanoma with BRAF V600 mutation. Purpose of this report is to describe the combination in terms of clinical efficacy, safety, and economic impact. In particular, a cost-effectiveness analysis and a budget impact analysis were performed in order to evaluate the combination versus monotherapy and the financial sustainability of trametinib + dabrafenib on the Italian market. [In Italian]